Math, asked by Rahuldebnath92, 1 year ago


15. If (x-1) is a factor of x2 + x - 2 then the other factor will be
_____​

Answers

Answered by HariesRam
5

Answer:

by \: factorising \\  {x}^{2}  + x - 2 = 0 \\  (x - 1)(x + 2) = 0 \\  \\ so \: the \: other \: factor \: is \: (x + 2)

Hopes it helps

Please mark as brainliest

Answered by Anonymous
0

Answer:

x-1 is one of the factor

so make g(x) = x-1

p(x) = +x-2

divide p(x) with g(x)

x-1 ) +x-2 ( x+2

-x

-----------

2x-2

2x-2

-------------

0

the other factor is x+2

Similar questions